ANALISIS STRATEGI PEMASARAN POLIS ASURANSI KENDARAAN BERMOTOR - Winanto Nawarcono; Arif Raharja (Jurnal Solusi, 2022)
The increasing competition in the general insurance business in Indonesia is getting tougher, each of which implements different marketing strategies to compete with each other and dominate the wider market. In order for the company to survive and be able to compete, it is necessary to apply an appropriate strategy using a SWOT analysis. This study aims to identify and analyze the strengths, weaknesses, opportunities, threats and marketing strategies at PT Pan Pacific Yogyakarta Branch. This study uses descriptive qualitative research methods, namely data collection to test hypotheses or answer questions about the current status of research subjects. The analysis method used is the SWOT analysis using the EFE (external factor analysis) and IFE (internal factor analysis) method of the company which is then evaluated by the SWOT matrix. The results showed that PT Pan Pacific Insurance Yogyakarta branch was in prime condition with a coordinate point (1.65 : 1.65) with this condition the company implemented SO strategy with a score of 7.11. This shows the opportunities and strengths that have a huge influence on the company despite the weaknesses and threats that always exist in business